STRATEGI PENGELOLAAN EKOSISTEM HUTAN MANGROVE DI NEGERI AMAHAI - Ely, Achmad J; Tuhumena, Lolita; Sopaheluwakan, Juanita; Pattinaja, Yvonne (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2021)
Mangrove forest is a very productive and beneficial ecosystem. Mangrove forest resources in Amahai Village will be increasingly exploited along with the increasing population and economic pressure. The aim of this research is to identify the forms of use by the community in the mangrove area, and to recommend mangrove ecosystem management strategies in Amahai Village. This research was conducted in the mangrove forest area of ​​Amahai Village, Central Maluku Regency from September to November 2018. Sampling was carried out by purposive sampling technique of 36 respondents. The analytical method used is data analysis of descriptive qualitative to identify forms of utilization by the community. SWOT analysis is used to analyze the management strategies of mangrove ecosystem on Amahai Village by identifying internal strengths and weaknesses as well as opportunities external threats. The results obtained five forms of utilization carried out in the mangrove area of ​​Amahai Village, those are fishing, collecting sea cucumbers, gleaning shellfish (bameti), tourism (recreation), and research. There are eight management strategies produced, namely 1) implementing government policies to maintain the potential of mangrove ecosystem resources in order to meet community needs and regional income; 2) utilizing the potential of mangrove ecosystem resources for ecotourism activities and support science and technology; 3) revitalization of customary institutions as an effort to manage mangrove ecosystem areas; 4) organizing resource processing activities in the mangrove ecosystem to meet nutritional needs and increase community income; 5) development of mangrove areas with an environmental insight; 6) improving MCS (Monitoring, Controling and Surveillance); 7) improving coordination among stakeholders; and 8) increasing community knowledge and awareness about the function of mangrove ecosystems and the skills of the communities around the mangrove area. ABSTRAK Hutan mangrove merupakan suatu ekosistem yang sangat produktif dan memberikan manfaat. Sumberdaya hutan mangrove di Negeri Amahai akan semakin tereksploitasi seiring dengan meningkatnya jumlah penduduk dan desakan ekonomi. Tujuan penelitian ini adalah untuk mengidentifikasi bentuk-bentuk pemanfaatan yang dilakukan oleh masyarakat di kawasan mangrove, serta merekomendasikan strategi pengelolaan ekosistem mangrove di Negeri Amahai. Penelitian ini dilaksanakan di kawasan hutan mangrove Negeri Amahai, Kabupaten Maluku Tengah pada bulan September hingga November 2018. Pengambilan sampel dilakukan dengan teknik purposive sampling terhadap responden sebanyak 36 orang. Metode analisis yang digunakan adalah analisis data deskriptif kualitatif untuk mengidentifikasi bentuk-bentuk pemanfaatan yang dilakukan masyarakat. Analisa SWOT digunakan untuk menganalisis strategi pengelolaan ekosistem mangrove Negeri Amahai dengan mengideintifikasi kekuatan dan kelemahan internal serta peluang dan ancaman eksternal. Hasil penelitian diperoleh lima bentuk pemanfaatan yang dilakukan pada kawasan mangrove Negeri Amahai yaitu penangkapan ikan, pengumpulan teripang, bameti, wisata (rekreasi), serta penelitian. Terdapat delapan strategi pengelolaan yang dihasilkan yaitu 1) mengimplementasikan kebijakan pemerintah untuk menjaga potensi sumberdaya ekosistem mangrove guna pemenuhan kebutuhan masyarakat dan pendapatan daerah; 2) memanfaatkan potensi sumberdaya ekosistem mangrove untuk kegiatan ekowisata serta mendukung ilmu pengetahuan dan terknologi; 3) revitalisasi kelembagaan adat sebagai upaya mengelola kawasan eksoistem mangrove; 4) menyelenggarakan kegiatan pengolahan sumberdaya pada ekosistem mangrove untuk memenuhi kebutuhan gizi dan meningkatkan pendapatan masyarakat; 5) pengembangan kawasan mangrove yang berwawasan lingkungan; 6) peningkatan monitoring, controling and surveilance; 7) meningkatkan koordinasi antar stakeholder; dan 8) meningkatkan pengetahuan dan kesadaran masyarakat tentang fungsi ekosistem mangrove serta keterampilan masyarakat sekitar daerah mangrove Kata Kunci: Strategi pengelolaan, ekosistem mangrove, SWOT, keberlanjutan, Negeri Amahai